Preparing for the worst : - Vinod, Hrishikesh D. (John Wiley & Sons, 2005)
Stock market investors have very different reactions to downside versus upside risk. This book begins by explaining the current treatment of stock market risk and methods of lowering that risk. The authors go on to show that many types of asymmetry of stock returns or investor reactions cause the existing theory to fail. They present innovative downside risk and utility theories to account for these asymmetries, demonstrating how the traditional model can be adjusted for downside risk.